Solid titanium catalyst component, process for its preparation and catalyst and use thereof

CN122940927APending Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202510465295.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

值得注意的是,虽然可以通过烷基铝的种类以及与催化剂的比例调整共聚单体的插入,但是只是在有限的范围内调控

Benefits of technology

[0084]本发明制备的固体钛催化剂组份中的微粒子少,有利于在烯烃聚合过程中使聚合物微粒减少。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005358612870000071
    Figure BDA0005358612870000071
  • Figure BDA0005358612870000211
    Figure BDA0005358612870000211
  • Figure BDA0005358612870000221
    Figure BDA0005358612870000221
Patent Text Reader

Abstract

This invention discloses a solid titanium catalyst composition, its preparation method, and its application, relating to the field of α-olefin polymerization technology. The catalyst composition is prepared from raw materials comprising the following components: magnesium halide, titanium-containing compound, solvent, inorganic oxide support filler, electron donor compound, and inert organic compound. Based on a total weight of 100 wt% of the catalyst composition, the titanium content is 0.1–5 wt%; the molar ratio of magnesium to titanium is greater than 2:1; the molar ratio of solvent to magnesium is less than 3:1; the molar ratio of electron donor compound to magnesium is less than 3:1; the weight ratio of inert organic compound to magnesium halide is less than 5:1; and the weight ratio of inorganic oxide support filler to magnesium halide is less than 4:1. The catalyst of this invention, when used to catalyze the polymerization of ethylene and α-olefins, exhibits high activity, low fine powder content, high bulk density, and low polyethylene resin density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of α-olefin polymerization technology, and more specifically, to a solid titanium catalyst component, its preparation method, the catalyst, and its application. Background Technology

[0002] As is well known, highly efficient Ziegler-Natta catalysts for olefin polymerization consist of two parts: a main catalyst and a co-catalyst. The main catalyst is composed of transition metal compounds located in Groups 4 to 8 of the periodic table, while the co-catalyst is an organometallic compound located in Groups 1 to 3 of the periodic table. Typically, the main catalyst can be further divided into two parts: an inert support and the active component it supports. The main catalyst is generally prepared by reacting titanium halides with magnesium halides containing lattice defects, or by loading the reactants onto an inert support. Magnesium halides with lattice defects are preferred. These lattice defect magnesium halides can be generated from magnesium compounds, or by reacting magnesium halides with electron donors such as alcohols, ethers, or esters, followed by the removal of some of the electron donors.

[0003] In the polymerization of ethylene or the copolymerization of ethylene with α-olefins, the performance of the catalyst directly affects the properties of the polymer. High catalytic activity combined with good hydrogen regulation is desirable in polymerization, especially under conditions of a higher hydrogen / olefin ratio. High catalytic activity is beneficial for the production of resins with higher melt index, particularly those with higher melt index and higher density. High catalytic activity combined with good copolymerization properties is also desirable, as this facilitates the production of lower density resins. Good copolymerization properties also reduce the amount of comonomer required to produce resins of the same density, thus improving the flowability of the resin powder and enabling stable production at higher loads. Lower catalyst particle content is desirable, as it helps reduce agglomeration on the equipment walls and improves the flowability of the resin powder. Lower solvent content is desirable, as high solvent content requires a higher amount of alkylaluminum co-catalyst during polymerization, increasing both costs and the residual aluminum content in the resin, leading to higher resin ash content and increased haze during film production. It is desirable to have appropriate electron donors and their content, so as to improve the copolymerization performance of the catalyst while ensuring its overall performance.

[0004] During polymerization, polymer particles primarily originate from particles within the catalyst, active particles within the catalyst, and catalyst breakage generated during polymerization. Polymer particles are detrimental to the polymerization process because they can cause equipment malfunctions, impaired operability, and reduced efficiency. Therefore, minimizing polymer particles during olefin polymerization is desirable. One method to reduce these particles is by eliminating or reducing the catalyst particles that generate them. A higher bulk density of the polymer powder is also desirable during polymerization; a moderately high polymer powder bulk density allows for more stable control of the polymerization reactor.

[0005] In existing technologies, such as Chinese patents CN1958620A, CN102295717A, and CN103772536A, a precipitation method in solution is used to introduce siloxane-based electron donors, ortho-alkoxy-substituted benzoic acid ester / carboxylic acid ester (or diether) complex electron donors, and benzoic acid ester-based electron donors, respectively, to improve the hydrogen sensitivity of the catalyst. For example, Chinese patent CN102807638A uses an impregnation loading method, introducing a complex of long-chain monoesters / short-chain monoesters as electron donors into a spherical support for magnesium chloride-alcohol adduct formed by high-speed stirring and low-temperature condensation to improve the catalyst activity. For example, Chinese patent CN1103406A uses an external electron donor method, introducing diethers, especially 1,3-diethers, into the polymerization reactor simultaneously with the catalyst to obtain polyethylene products with a narrower molecular weight distribution. For example, patent EP0219998A1 uses a precipitation-sedimentation method in solution. After obtaining a particulate suspension, an appropriate amount of water, an electron donor, is introduced to improve the particle size and distribution of the resulting polyethylene powder and reduce the content of fine powder. Chinese patents CN1726230A, CN1798774A, and CN101050248A use an impregnation-loading method. Electron donors such as alcohols, ketones, amines, amides, nitriles, alkoxysilanes, aliphatic ethers, and aliphatic carboxylic acid esters are introduced into a spherical support for magnesium chloride-alcohol adducts formed by high-speed stirring and low-temperature condensation to improve the copolymerization performance of the catalyst. Patent WO2021115929A1 uses a spherical support for magnesium chloride-alcohol adducts formed by high-speed stirring and low-temperature condensation, impregnated with a titanium compound, followed by washing and the addition of a guanidine compound as an internal electron donor, to obtain a near-spherical catalyst. This catalyst exhibits the ability to uniformly distribute comonomers in the preparation of ethylene copolymers. In the process of preparing spherical supports for magnesium chloride-alcohol adducts using high-speed stirring and low-temperature condensation, other liquid organic compounds must be used, increasing reagent consumption and complicating subsequent liquid-solid separation steps. For example, Czaja reported in Polymer (Polymer, 2000, 41, 7899-7904) on the copolymerization of ethylene and 1-octene using a vanadium-based catalyst MgCl2(THF)2 / VCl4 / Et2AlCl, achieving an 1-octene insertion rate of 0.47% in the copolymer. Under the same polymerization conditions, the copolymer obtained using a titanium-based catalyst had an 1-octene insertion rate of 0.39%. Boisson reported in ACS Catalysis (ACS Catal. 2020, 10, 7216-7229) that the amount of triethylaluminum co-catalyst can not only regulate the copolymerization kinetics but also has a significant impact on the distribution of comonomers in the polymer chain. As proposed in patent US20120053308A1, the type of alkylaluminum can adjust the distribution of comonomers in the polymer chain.It is worth noting that although the insertion of comonomers can be adjusted by the type of alkylaluminum and its ratio with the catalyst, this adjustment is only within a limited range. Chinese patents CN101885793A and CN101885795A utilize composite electron donors containing organothiols and organosilicamines to improve the copolymerization performance of catalysts. However, the synthesis steps of these catalysts are relatively cumbersome, and the organothiols and organosilicamines used have unpleasant odors and are expensive. For example, Chinese patent CN104211844A discloses a gas-phase fluidized bed LLDPE catalyst, its preparation method, and its application. This catalyst uses porous silica gel and anhydrous magnesium chloride as supports, with a titanium-containing transition metal supported on the porous silica gel and magnesium chloride composite support as the active component, and an electron donor compound as a modifier. The supported components account for 1.00–5.00% of the total mass of the catalyst, Ti: 15.20–32.35%, Cl: 1.35–6.52%, electron donor: 0.10–5.78%, and the remainder is silica gel. The catalyst is prepared as follows: An alkane solvent, anhydrous magnesium chloride, and an organic alcohol are reacted at a certain temperature for a certain time to obtain homogeneous reactant A; an electron-donating compound is added to the above reactant A solution to obtain reactant B, wherein the electron-donating compound is a silane, ester, ether, amine, ketone, or a mixture of different electron-donating compounds; silica gel (pre-activated in a muffle furnace at 200°C for 2 hours under nitrogen protection, and then activated at 600°C for 4 hours) is added to reactant B to obtain reactant C; reactant C is slowly cooled to -5°C, titanium tetrachloride compound is slowly added dropwise, and the reaction is carried out at this temperature for a certain time, then the temperature is slowly increased and kept constant at a certain temperature. After the reaction is completed, the upper liquid is removed by filtration to obtain reactant D. Reactant D is heated with toluene and then washed with n-hexane, and finally dried with high-purity nitrogen to obtain a solid powder catalyst. The aim is to provide a catalyst composition for the gas-phase fluidized bed method to prepare LLDPE, thereby enabling the catalyst system to possess high activity, high copolymerization, and hydrogen-modulated sensitivity, and producing polyethylene products with good morphology, uniform particle size, and high bulk density. Furthermore, by adding different electron donors during catalyst preparation, polyethylene resins with adjustable molecular weight and molecular weight distribution can be produced, thereby improving product performance, enhancing resin processability, and broadening the product's application areas. However, the titanium loading process in this catalyst synthesis step requires a large amount of titanium tetrachloride, as well as large amounts of toluene and hexane for hot washing. The recovery of toluene, hexane, and titanium tetrachloride is complex, resulting in high energy and material consumption in the catalyst production process, and also causing environmental pollution.

[0006] Spray drying is an effective method for preparing highly efficient Ziegler-Natta catalysts for olefin polymerization. This method involves spraying a dissolved liquid or suspension through specially designed nozzles into a hot, inert gas drying chamber, where the dispersed microdroplets are dried into powder or granular products. Once the droplets come into contact with the drying carrier gas, evaporation occurs on a rapidly established saturated vapor film on the droplet surface. During evaporation, the droplet size distribution changes, resulting in different products exhibiting different characteristics. During evaporation, droplets are prone to expansion, collapse, breakage, or fragmentation, leading to porous, irregular shapes, which is related to the droplet characteristics formed in the spray process. Changes in droplet composition, volume, and size can influence particle structure modification. By adjusting the conditions of the spray drying process, large, small, or aggregated particles can be obtained.

[0007] For example, US4421674A discloses a process for preparing spherical MgCl2 supported polyolefin catalysts using spray drying: 1) Preparation of mother liquor for spray drying: MgCl2 is dissolved in ethanol to achieve a solution concentration of 100–300 g MgCl2 / L solution, with a water content not exceeding 5%; 2) Preparation of spherical MgCl2 support by spray drying: The drying process and the inert gas used for spray drying are both N2, with a purity greater than 99%. The inlet temperature of the spray dryer is set between 180 and 280°C, and the supply of mother liquor and N2 gas is controlled to ensure that the outlet temperature of the instrument is at least 40°C lower than the inlet temperature and stabilized between 130 and 210°C. The resulting solid product is collected to obtain spherical MgCl2 particles, with an alcohol content of 12%–25 wt% for the spherical MgCl2 support; 3) Titanium loading process: The spherical MgCl2 obtained in step 2) is contacted with gaseous or liquid titanium halides under certain conditions until the titanium content on the spherical support reaches 0.7–12%. This method involves the stepwise preparation of the support and catalyst. The solvent used in supporting preparation is an alcohol containing active hydrogen, such as ethanol, which necessitates a distributed process for titanium loading. Furthermore, it requires a large amount of gaseous or liquid titanium halides, necessitating the recovery and purification of excess titanium halides, making the preparation process long and complex. Additionally, the catalyst supported on the spherical MgCl2 particles is prone to breakage when used directly. For example, Chinese patent CN1668654A discloses a spray-dried polymerization catalyst and a polymerization method using this catalyst. The catalyst comprises an inert porous packing material and a spray-dried composition of the following reaction products: magnesium halide, solvent, electron donor compound, a mixture of transition metal compounds, or reaction products. This catalyst contains an alcohol compound as an electron donor and uses spherical inert porous packing material with an average particle size of 1μm to 12μm. This method aims to reduce the particulate content in the polymer by reducing small catalyst particles in the catalyst. For example, Chinese patent CN1993391A discloses a Ziegler-Natta catalyst composition for strong spray drying. This catalyst comprises an inert porous packing material, magnesium halide, a solvent or diluent, a Lewis base electron donor compound, a mixture of transition metal compounds, or reaction products. The magnesium halide compound is present in the solvent or diluent at at least 90% of its saturation concentration, and the electron donor compound used is an alcohol or tetrahydrofuran. The catalyst particles obtained after spray drying have an average diameter (D50) of 10–70 μm, wherein at least 5% of the particles have an internal void volume substantially or completely surrounded by a single surface layer (shell). This layer is characterized in that particles with a diameter greater than 30 μm have an average shell thickness / particle size ratio (thickness ratio) greater than 0.2 as measured by SEM. This catalyst reduces polymer particles by minimizing catalyst breakage or ensuring that the catalyst fragments remain relatively large after breakage. For example, Chinese patent CN1085915A discloses a method for preparing a Ziegler-Natta catalyst system.TiCl3 tetrahydrofuran solution was prepared by reducing titanium tetrachloride with metallic magnesium in tetrahydrofuran. Magnesium chloride was then dissolved in tetrahydrofuran. The two solutions were thoroughly mixed, and unreacted magnesium and undissolved magnesium chloride were filtered off. The filtered solution was then thoroughly mixed with silica gel and spray-dried to obtain dispersed catalyst particles. This catalyst has a high titanium content and high activity, and can significantly reduce the hexane extractability during the polymerization of ethylene and α-olefins. However, at higher yields during catalyst preparation, its D10 is relatively small. Maintaining a larger D10 requires reducing the overall catalyst yield, which results in more catalyst particles, increasing production costs and generating more waste. For example, Chinese patent CN104761665A discloses a spray-dried Ziegler-Natta catalyst composition, which includes inorganic oxide particles, magnesium halide, an electron donor compound, a silane coupling agent, and titanium halide. The electron donor compound is selected from an alcohol or an ether, or a mixture thereof. The silane coupling agent improves the surface properties of the silica support, and the catalyst exhibits high activity, good hydrogen sensitivity, and low fine powder content. For example, Chinese patent CN1668654A discloses a spray-dried polymerization catalyst and a polymerization method using the catalyst. The catalyst comprises an inert porous filler and a spray-dried composition of the following reaction products: magnesium halide, solvent, electron donor compound, a mixture of transition metal compounds, or reaction products. The electron donor compound improves the solubility of magnesium halide in the electron donor solvent, such that the solubility does not decrease over any temperature interval up to the boiling point of the electron donor solvent. The electron donor compound used herein does not include the solvent, even when such a solvent has electron donor characteristics. Examples of electron donor compounds include alcohols, thiols, weakly contributing amines, and phosphine. The catalyst exhibits improved activity; spherical inert porous packing with an average particle size of 1μm to 12μm is used to reduce small catalyst particles in the catalyst, thereby reducing the particulate content in the polymer, but the hydrogen regulation performance is not improved.

[0008] The aforementioned Ziegler-Natta type olefin polymerization catalysts have improved in one or more aspects of performance parameters such as catalyst activity, hydrogen sensitivity, copolymerization performance, bulk density of polymer powder, melt index and melt flow ratio, fine powder content, and copolymer unit distribution, but they are still not ideal. In order to better meet the needs of industrial production and obtain lower-density polyolefin products with better performance, it is necessary to develop a catalyst with better copolymerization performance and good overall performance. Summary of the Invention

[0009] To address the problems existing in the prior art, this invention provides a solid titanium catalyst component, its preparation method, the catalyst itself, and its applications. The solid titanium catalyst component of this invention is prepared by dissolving magnesium halide and titanium-containing compounds in a solvent, and adding a certain proportion of electron donor compounds, inert organic compounds, and inorganic oxide support fillers to form a suspension. The resulting suspension is then spray-dried to obtain a near-spherical solid titanium catalyst component. When the catalyst containing the solid titanium catalyst component of this invention is used to catalyze the polymerization of ethylene and α-olefins, it exhibits high activity, low fine powder content in the resulting polyethylene powder, high bulk density, and low polyethylene resin density.

[0010] One of the objectives of this invention is to provide a solid titanium catalyst composition.

[0011] The solid titanium catalyst component of the present invention is prepared from raw materials comprising the following components:

[0012] Magnesium halides, titanium-containing compounds, solvents, inorganic oxide carrier fillers, electron-donating compounds, and inert organic compounds;

[0013] Based on a total weight of 100 wt% of the catalyst components, the content of titanium is 0.1 to 5 wt%.

[0014] The molar ratio of magnesium to titanium is greater than 2:1;

[0015] The molar ratio of solvent to magnesium is less than 3:1;

[0016] The molar ratio of the electron-donating compound to magnesium is less than 3:1;

[0017] The weight ratio of inert organic compounds to magnesium halides is less than 5:1;

[0018] The weight ratio of inorganic oxide carrier filler to magnesium halide is less than 4:1.

[0019] In a preferred embodiment of the present invention:

[0020] Based on a total weight of 100 wt% of the catalyst components, the content of titanium is 0.5 to 3 wt%.

[0021] The molar ratio of magnesium to titanium is (4-10):1;

[0022] The molar ratio of solvent to magnesium is (0.5~2):1;

[0023] The molar ratio of the electron-donating compound to magnesium is (0.1–1.5):1;

[0024] The weight ratio of inert organic compound to magnesium halide is (0.1–2):1;

[0025] The weight ratio of inorganic oxide carrier filler to magnesium halide is (0.5~2):1.

[0026] In a preferred embodiment of the present invention:

[0027] The catalyst component is a spherical solid particle; preferably, the average diameter of the catalyst component is 2 to 100 μm, more preferably 18 to 30 μm; more preferably, the ratio of the short axis to the long axis of the catalyst component is ≥0.67, more preferably ≥0.77, and particles of this morphology have better performance.

[0028] In a preferred embodiment of the present invention:

[0029] The structural formula of the electron donor compound is:

[0030]

[0031] Wherein, X1, X2, X3, X4, and X5 are each independently one of hydrogen, halogen, C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C1-C10 aryl, and C1-C10 aralkyl, and R is one of C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C1-C10 aryl, and C1-C10 aralkyl; preferably,

[0032] The electron-donating compound is anisole, o-chloroanisole, p-chloroanisole, 2,4-dichloroanisole, m-chloroanisole, o-fluoroanisole, p-fluoroanisole, 2,4-difluoroanisole, m-fluoroanisole, o-bromoanisole, p-bromoanisole, 2,4-dibromoanisole, m-bromoanisole, phenethyl ether, o-chloroanisole, p-chloroanisole, 2,4-dichloroanisole, m-chloroanisole, o-fluoroanisole, p-fluoroanisole. Ethers, 2,4-difluorophenylethyl ether, m-fluorophenylethyl ether, o-bromophenylethyl ether, p-bromophenylethyl ether, 2,4-dibromophenylethyl ether, m-bromophenylethyl ether, isopropyl phenyl ether, o-chlorophenyl isopropyl ether, p-chlorophenyl isopropyl ether, 2,4-dichlorophenyl isopropyl ether, m-chlorophenyl isopropyl ether, o-fluorophenyl isopropyl ether, p-fluorophenyl isopropyl ether, 2,4-difluorophenyl isopropyl ether, m-fluorophenyl isopropyl ether, o-bromophenyl isopropyl ether, p-bromophenyl isopropyl ether, 2,4-Dibromophenylisopropyl ether, m-bromophenylisopropyl ether, phenylbutyl ether, o-chlorophenylbutyl ether, p-chlorophenylbutyl ether, 2,4-dichlorophenylbutyl ether, m-chlorophenylbutyl ether, o-fluorophenylbutyl ether, p-fluorophenylbutyl ether, 2,4-difluorophenylbutyl ether, m-fluorophenylbutyl ether, o-bromophenylbutyl ether, p-bromophenylbutyl ether, 2,4-dibromophenylbutyl ether, m-bromophenylbutyl ether, tert-butyl phenyl ether, o-chlorophenyltert-butyl ether, p-chlorophenyltert-butyl ether The ether is at least one of the following: 2,4-dichlorophenyl tert-butyl ether, m-chlorophenyl tert-butyl ether, o-fluorophenyl tert-butyl ether, p-fluorophenyl tert-butyl ether, 2,4-difluorophenyl tert-butyl ether, m-fluorophenyl tert-butyl ether, o-bromophenyl tert-butyl ether, p-bromophenyl tert-butyl ether, 2,4-dibromophenyl tert-butyl ether, m-bromophenyl tert-butyl ether, diphenyl ether, and phenyl benzyl ether; more preferably, at least one of anisole, o-chloroanisole, isopropyl phenyl ether, and diphenyl ether.

[0033] In this invention, the aforementioned electron-donating compound can increase the surface tension of droplets during the spray drying evaporation process, thereby inhibiting the expansion, collapse, breakage, or splitting of droplets, thus reducing the generation of porous, irregularly shaped catalyst component particles, and consequently reducing the content of polymer fine powder caused by excessive polymer particles during polymerization. At the same time, it can modulate the electronic characteristics and spatial morphology of the catalyst active center, which is beneficial to improving the copolymerization performance of the catalyst and reducing the density of the resulting polymer.

[0034] In a preferred embodiment of the present invention:

[0035] The titanium-containing compound is at least one of titanium halide and a product of metal reduction of titanium halide; preferably,

[0036] The titanium halide is at least one selected from titanium tribromide, titanium tetrabromide, titanium trichloride, and titanium tetrachloride; and / or,

[0037] The product of the metal reduction of titanium halide is at least one of the products of aluminum reduction of titanium halide, magnesium reduction of titanium halide, iron reduction of titanium halide, and zinc reduction of titanium halide. Of course, reduced titanium halide obtained by reducing titanium tetrachloride with other metals can also be used; more preferably,

[0038] The chemical formula of the product of aluminum reduction of titanium halide is TiXm·nAlXp, where 0<n≤1, 0<m≤3, 0<p≤3, and X is bromine or chlorine, such as TiCl3·1 / 3AlCl3; and / or,

[0039] The chemical formula of the product of magnesium reducing titanium halide is TiXm'·qMgXr, where 0<q≤1, 0<m'≤3, 0<r≤2, and X is bromine or chlorine, such as TiCl3·1 / 2MgCl2.

[0040] In a preferred embodiment of the present invention:

[0041] The magnesium halide is at least one of magnesium dichloride, magnesium dibromide, and magnesium diiodide; and / or...

[0042] The inorganic oxide carrier filler is an oxide of silicon and / or an oxide of aluminum, preferably silicon dioxide; more preferably, the particle size of the inorganic oxide carrier filler is 0.01–10 micrometers, preferably 0.01–5 micrometers; even more preferably, the water content of the inorganic oxide carrier filler is 0–2.5%, preferably 0–0.6%; and / or,

[0043] The present invention uses silicon oxide and / or aluminum oxide as inorganic oxide support filler, which helps to control the shape and composition of catalyst particles during spray drying, and the resulting catalyst particles have good shape, high strength and are not easily broken.

[0044] As a preferred option, regardless of the type of inorganic oxide carrier filler (filler) chosen, it should be dry, i.e., free of absorbed moisture; the filler is dried by heating for a period of time at a temperature below the sintering or melting point of the filler material (however, some fillers, such as pyrolytic silica, naturally have low residual moisture content due to their specific manufacturing methods); typically, drying is carried out at a temperature of at least 100°C, and lower temperatures may be used when extended drying times are acceptable or when the filler has a low melting or sintering temperature; inorganic filler materials are typically dried at temperatures between 200 and 800°C; simultaneously, the filler material may be treated with, optionally 1 to 10 wt%, one or more Lewis acids (e.g., trialkylaluminum compounds or organosilanes) to remove polar impurities including water or hydroxyl groups;

[0045] The solvent is a solvent capable of dissolving the magnesium halide and the titanium-containing compound, preferably at least one selected from diethyl ether, propyl ether, isopentyl ether, tetrahydrofuran, methyltetrahydrofuran, and dioxane; more preferably tetrahydrofuran and / or methyltetrahydrofuran; and / or,

[0046] The inert organic compound is a liquid hydrocarbon and / or silicone oil; preferably,

[0047] The liquid hydrocarbon is a C7-C31 alkane with a kinematic viscosity of 1.0-500 mmHg at 40°C. 2 At least one of the white oils with a kinematic viscosity of 60-80 mm at 40°C is preferred. 2 / s of white oil; and / or,

[0048] The silicone oil has a kinematic viscosity of 5.0-5000 mm at 25°C. 2 / s, preferably at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, ethyl hydrogen silicone oil, and hydroxy hydrogen silicone oil;

[0049] The inert organic compound can modulate the viscosity of the mother liquor and suspension, thereby reducing the generation of catalyst particles and thus eliminating or reducing polymer fines.

[0050] A second objective of this invention is to provide a method for preparing a solid titanium catalyst component as described in one objective of this invention.

[0051] The method for preparing the solid titanium catalyst component of the present invention includes:

[0052] The catalyst component is prepared by mixing magnesium halide, titanium-containing compound, solvent, inorganic oxide support filler, electron donor compound and inert organic compound to form a suspension, followed by spray drying.

[0053] In a preferred embodiment of the present invention, the method includes:

[0054] (1) Preparation of mother liquor: Under a protective gas atmosphere, solvent, magnesium halide, titanium-containing compound, electron donor compound and inert organic compound are brought into contact to obtain mother liquor;

[0055] (2) Carrier mixing: In the protective gas atmosphere, inorganic oxide carrier filler is added during or after step (1) to mix and obtain slurry suspension;

[0056] (3) Spray forming: The slurry suspension is spray dried to obtain the catalyst component.

[0057] According to the present invention, the reaction products of the magnesium halide, titanium-containing compound, solvent, electron donor compound, and inert organic compound are loaded onto the inorganic oxide support filler to form particles of the solid titanium catalyst component. The inorganic oxide support filler can be added at any time during the preparation of the mother liquor. For example, the magnesium halide, titanium-containing compound, inorganic oxide support filler, electron donor compound, and inert organic compound are mixed and reacted in a solvent to obtain a slurry suspension, which is then spray-dried. Preferably, the support mixing involves mixing the mother liquor obtained in step (1) with the inorganic oxide support filler to obtain a slurry suspension.

[0058] In a preferred embodiment of the present invention:

[0059] The molar ratio of the magnesium halide to the titanium-containing compound is greater than 2:1, preferably (4-10):1; and / or,

[0060] The molar ratio of the solvent to magnesium halide is less than 240:1, preferably (20-40):1; the amount of solvent added is such that it can fully dissolve the magnesium halide and the titanium-containing compound, and that the magnesium halide, the titanium-containing compound, the solvent, the inorganic oxide carrier filler, the electron donor compound, and the inert organic compound come into contact to form a relatively stable suspension; and / or,

[0061] The molar ratio of the electron donor compound to magnesium halide is less than 3:1, preferably (0.1–1.5):1; and / or,

[0062] The weight ratio of the inert organic compound to magnesium halide is less than 5:1, preferably (0.1–2):1; and / or,

[0063] The weight ratio of the inorganic oxide carrier filler to magnesium halide is less than 4:1, preferably (0.5 to 2):1.

[0064] In a preferred embodiment of the present invention:

[0065] In step (1): the contact temperature is 5℃~85℃, and / or the time is ≥0.1 hours; and / or,

[0066] In step (2): the mixing temperature is 5℃~85℃, and / or the time is ≥0.1 hours; and / or,

[0067] In step (3): the inlet temperature of the spray dryer is 100–240°C, preferably 120–160°C, and / or the outlet temperature is 60–130°C, preferably 90–115°C, and / or the material feed flow rate is 1–30 ml / min, preferably 5–15 ml / min, and / or the carrier gas and the spray gas can be the same or different, and are independently protective gases, preferably nitrogen, and / or the carrier gas flow rate is 2–40 ml / min. 3 / h, preferably 20-30m 3 / h, and / or, the spray gas flow rate is 5 to 800 L / h, preferably 200 to 500 L / h.

[0068] A third objective of this invention is to provide a catalyst for olefin polymerization reactions.

[0069] The catalyst for olefin polymerization according to the present invention comprises a solid titanium catalyst component as described in one objective of the present invention or a solid titanium catalyst component and a co-catalyst prepared by the method described in another objective of the present invention.

[0070] The cocatalyst is an organoaluminum compound and / or an incomplete hydrolysis product of an organoaluminum compound (such as methylaluminoxane, etc.);

[0071] The molar ratio of aluminum in the co-catalyst to titanium in the solid titanium catalyst component is (1-1000):1, preferably (5-200):1.

[0072] In a preferred embodiment of the present invention:

[0073] The chemical formula of the organoaluminum compound is AlR' b X' 3-b Wherein, R' is hydrogen or a C1-C20 hydrocarbon group, preferably a C1-C6 hydrocarbon group, 0 < b ≤ 3, preferably 1 < b ≤ 3, and X' is a halogen, preferably one of chlorine, bromine, and iodine; more preferably,

[0074] The organoaluminum compound is at least one of trimethylaluminum, triethylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, ethyl sesquichloride (a mixture of diethylaluminum chloride and diethylaluminum chloride), and dimethylaluminum chloride.

[0075] To make the solid titanium catalyst component of the present invention suitable for the production of ethylene polymers, it is necessary to activate the solid titanium catalyst component using an activator component as a co-catalyst. Preferably, the solid titanium catalyst component obtained by the present invention is reacted with a co-catalyst in a hydrocarbon solvent to obtain a catalyst; or the solid titanium catalyst component obtained by the present invention is reacted with a co-catalyst during the polymerization process to initiate an olefin polymerization reaction.

[0076] The fourth objective of this invention is to provide an application of the catalyst for olefin polymerization as described in the third objective of this invention in olefin polymerization.

[0077] The application of the catalyst for olefin polymerization described in this invention in olefin polymerization yields polyethylene resin with lower density; preferably,

[0078] The polymerization method for the olefin polymerization can be carried out according to available technologies, preferably one of the following: gas-phase polymerization, slurry polymerization, and solution polymerization; and / or,

[0079] The reaction temperature for the olefin polymerization reaction is 20–120°C, preferably 65–105°C; and / or,

[0080] The olefin polymerization reaction is a homopolymerization of ethylene or a polymerization reaction of ethylene with at least one α-olefin, preferably a polymerization reaction of ethylene with at least one α-olefin; more preferably,

[0081] The α-olefin is at least one selected from propylene, butene, pentene, hexene, octene, decene, and 4-methyl-1-pentene.

[0082] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In the following, various technical solutions can, in principle, be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.

[0083] Compared with existing technologies, the present invention has the following advantages:

[0084] The solid titanium catalyst prepared by this invention has fewer microparticles, which is beneficial for reducing polymer particles during olefin polymerization.

[0085] The catalyst of the present invention, when used for olefin polymerization, exhibits high catalyst activity, low density of the resulting ethylene-α-olefin copolymer (in the prior art, under the same conditions, it is very difficult for Ziegler-Natta catalyst to reduce resin density), high polymer powder bulk density, and low polymer powder fine content. Detailed Implementation

[0086] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0087] It should also be noted that the various specific technical features described in the following embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the various possible combinations will not be described separately in this invention.

[0088] Furthermore, various embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention. The resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0089] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this invention are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0090] The testing methods used in the embodiments and comparative examples of this invention are as follows:

[0091] 1. Activity: Expressed as the weight of resin obtained per gram of catalyst over two hours;

[0092] 2. Polymer melt index (MI): Tested according to ASTM D1238-99, with a load of 2.16 kg and a temperature of 190°C;

[0093] 3. Apparent bulk density (BD) of polymer: Tested according to ASTM D1895-69 standard;

[0094] 4. Sieve analysis values: Tested according to ASTM D-1921 standard;

[0095] 5. Catalyst particle size: Measured using a MASTERSIZER2000 particle size analyzer, using the term D. 10 D 50 D 90 This refers to a specific percentage distribution of the standard logarithmic particle size distribution, such as catalyst particle size having a D...50 If the particle size is 24 μm, then the intermediate particle size is 24 μm; D 10 The 7μm indicates that 10% of the particles have a diameter of less than 7μm; D 90 The 45μm indicates that 90% of the particles have a diameter of less than 45μm;

[0096] 6. Titanium, magnesium, and chlorine content: determined using a Spectrumlab 752s UV-Vis spectrophotometer; the content of electron-donating compounds in the solid titanium catalyst component was determined using liquid NMR. 1 H-NMR determination;

[0097] 7. Polyethylene resin density: Tested according to ASTM D1505-2010 standard;

[0098] 8. THF content: Measured using an Agilent Technologies 7890A GC System.

[0099]

Example 1

[0100] (1) Preparation of solid titanium catalyst components

[0101] To a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging, add 100 ml tetrahydrofuran (THF), 4.0 g magnesium chloride, 0.91 ml TiCl4, 1.71 ml (13.8 mmol) o-methyl anisole, and 0.8 ml 68 g of sodium chloride in sequence while stirring. # White oil (kinematic viscosity 68.91 mmHg at 40℃) 2 The mixture was heated to 68°C with stirring, and then refluxed at this temperature for 3 hours to obtain the mother liquor. Throughout this process, the mixture was kept under a nitrogen atmosphere (<5ppm H₂O).

[0102] 5.7 g of silica gel (Cabot Corporation TS-610, particle size 0.1–1 μm, water content 0.2%) was added to a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging. The mother liquor was added while stirring, and the mixture was refluxed at 68 °C for 2 hours to ensure complete dispersion of the silica gel in the mother liquor, resulting in a slurry suspension. Throughout this process, a nitrogen atmosphere (<5 ppm H₂O) was maintained.

[0103] In a closed-loop recirculating spray dryer On the Mini Spray Dryer B-290, nitrogen gas at an inlet temperature of 145°C was introduced into the spray dryer. A slurry suspension at 43°C was added to the circulating dryer. The feed rate of the slurry suspension was adjusted to 7 mL / min, and the flow rate of the spray gas (N2) at room temperature was approximately 348 L / h. The flow rate of the carrier gas (N2) was adjusted to 27 mL / min. 3 The process was carried out at a rate of / h, with the outlet temperature set to 98℃, to obtain a solid titanium catalyst component in a collection bottle. The parameters of the obtained solid titanium catalyst component are shown in Table 1.

[0104] (2) Ethylene slurry polymerization

[0105] One liter of hexane was added to a 2-liter polymerization reactor that had been purged with nitrogen and then hydrogen. Simultaneously, 2 ml of 1M triethylaluminum hexane solution, 40 ml of 1-hexene, and 15 mg of the solid titanium catalyst component obtained in Example 1(1) were added. The temperature was raised to 85°C, and hydrogen was added to a pressure of 0.28 MPa. After hydrogenation, ethylene was added to a pressure of 1.03 MPa. The polymerization reaction was carried out at a constant temperature and pressure of 85°C and 1.03 MPa for 2 hours. Then the reaction was stopped, and the product was discharged after cooling. The polymerization results are shown in Table 2.

[0106]

Example 2

[0107] (1) Preparation of solid titanium catalyst components

[0108] To a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging, add 100 ml of tetrahydrofuran (THF) and 0.104 g of magnesium powder (average particle size 80–100 μm) sequentially with stirring. Then, slowly add 0.91 ml of TiCl4 over 0.5 hours. Heat to 50 °C and stir at this temperature for 4 hours. Next, add 3.59 g of magnesium chloride, raise the temperature to 68 °C and stir at this temperature for 2 hours. Finally, add 1.71 ml (13.8 mmol) of o-methyl anisole and 0.8 ml of 68... # White oil was refluxed at 68°C for 1 hour to yield a mother liquor containing tetrahydrofuran, magnesium chloride, magnesium-reduced titanium chloride, o-methyl anisole, and white oil. The entire process was carried out under a nitrogen atmosphere (<5 ppm H₂O).

[0109] Add 5.7 g of silica gel (Cabot Corporation TS-610, particle size 0.1–1 μm) to a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging. Add the aforementioned mother liquor while stirring, and continue reflux stirring at 68 °C for 2 hours to ensure complete dispersion of the silica gel in the mother liquor, resulting in a slurry suspension. Maintain a nitrogen atmosphere (<5 ppm H₂O) throughout this process.

[0110] In a closed-loop recirculating spray dryer On the Mini Spray Dryer B-290, nitrogen gas with an inlet temperature of 145°C was introduced into the spray dryer. The resulting slurry suspension at 43°C was added to the circulating dryer. The slurry suspension feed rate was adjusted to 6.2 mL / min, and the room temperature spray gas (N2) flow rate was approximately 330 L / h. The carrier gas (N2) flow rate was adjusted to 25 mL / min. 3 The process was carried out at a rate of 98°C per hour, and the solid titanium catalyst composition was obtained in a collection bottle. The parameters of the obtained solid titanium catalyst composition are shown in Table 1.

[0111] (2) Ethylene slurry polymerization

[0112] One liter of hexane was added to a 2-liter polymerization reactor that had been purged with nitrogen and then hydrogen. Simultaneously, 2 ml of 1M triethylaluminum hexane solution, 40 ml of 1-hexene, and 15 mg of the solid titanium catalyst component obtained in Example 2(1) were added. The temperature was raised to 85°C, and hydrogen was added to a pressure of 0.28 MPa. After hydrogenation, ethylene was added to a pressure of 1.03 MPa. The polymerization reaction was carried out at a constant temperature and pressure of 85°C and 1.03 MPa for 2 hours. Then the reaction was stopped, and the product was discharged after cooling. The polymerization results are shown in Table 2.

[0113]

Example 3

[0114] (1) Preparation of solid titanium catalyst components

[0115] To a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging, add 100 ml of tetrahydrofuran (THF), 4 g of magnesium chloride, and 1.64 g of TiCl3·1 / 3AlCl3 (8.27 mmol) (purchased from Toho Titanium Co., Ltd., Japan) sequentially with stirring. The mixture is heated to 68 °C with stirring and refluxed at this temperature for 3 hours. Then, add 1.71 ml (13.8 mmol) of o-methyl anisole and 0.8 ml of 68 °C... # White oil was refluxed at 68°C for 1 hour to obtain mother liquor. Throughout this process, the mixture was kept under a nitrogen atmosphere (<5ppm H₂O).

[0116] Add 5.7 g of silica gel (Cabot Corporation TS-610, particle size 0.1–1 μm) to a 250 ml four-necked flask equipped with a temperature controller, stirrer, reflux condenser, and protected by nitrogen purging. Add the aforementioned mother liquor while stirring, and continue reflux stirring at 68 °C for 2 hours to ensure complete dispersion of the silica gel in the mother liquor, resulting in a slurry suspension. Maintain a nitrogen atmosphere (<5 ppm H₂O) throughout this process.

[0117] In a closed-loop recirculating spray dryer On the Mini Spray Dryer B-290, nitrogen gas at an inlet temperature of 145°C was introduced into the spray dryer. A slurry suspension at 43°C was added to the circulating dryer. The feed rate of the slurry suspension was adjusted to 6 mL / min, and the flow rate of the spray gas (N2) at room temperature was approximately 330 L / h. The flow rate of the carrier gas (N2) was adjusted to 24 mL / min. 3 The process was carried out at a rate of 98°C per hour, and the solid titanium catalyst composition was obtained in a collection bottle. The parameters of the obtained solid titanium catalyst composition are shown in Table 1.

[0118] (2) Ethylene slurry polymerization

[0119] One liter of hexane was added to a 2-liter polymerization reactor that had been purged with nitrogen and then hydrogen. Simultaneously, 2 ml of 1M triethylaluminum hexane solution, 40 ml of 1-hexene, and 15 mg of the solid titanium catalyst component obtained in Example 3(1) were added. The temperature was raised to 85°C, and hydrogen was added to a pressure of 0.28 MPa. After hydrogenation, ethylene was added to a pressure of 1.03 MPa. The reaction was carried out at a constant temperature and pressure of 85°C and 1.03 MPa for 2 hours. The reaction was then stopped, and the product was discharged after cooling. The polymerization results are shown in Table 2.

[0120]

Example 4

[0121] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), the amount of o-methyl anisole added is changed from 1.71 ml (13.8 mmol) to 5 ml (40.4 mmol), and the rest is the same as Example 2.

[0122]

Example 5

[0123] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), the amount of o-methyl anisole added is changed from 1.71 ml (13.8 mmol) to 0.86 ml (6.9 mmol), and the rest is the same as Example 2.

[0124]

Example 6

[0125] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole was replaced with 1.75 ml (13.8 mmol) of o-chloro anisole. Everything else is the same as in Example 1.

[0126]

Example 7

[0127] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole is replaced with 1.61 ml (13.8 mmol) of 2,4-difluoroanisole. Everything else is the same as in Example 2.

[0128]

Example 8

[0129] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole was replaced with 1.88 g (13.8 mmol) of isopropyl phenyl ether. Otherwise, it is the same as Example 2.

[0130]

Example 9

[0131] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole is replaced with 2.35 g (13.8 mmol) of diphenyl ether. The rest is the same as in Example 2.

[0132]

Example 10

[0133] Compared with Example 2, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole is replaced with 1.5 ml (13.8 mmol) of anisole. Otherwise, it is the same as Example 2.

[0134]

Example 11

[0135] Compared with Example 3, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.64 g of TiCl3·1 / 3AlCl3 is changed to 0.82 g, and the rest is the same as in Example 3.

[0136]

Example 12

[0137] Compared with Example 3, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 1.64 g of TiCl3·1 / 3AlCl3 is changed to 3.28 g, and the rest is the same as in Example 3.

[0138]

Example 13

[0139] Compared with Example 3, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 4 grams of magnesium chloride is replaced with 5.3 grams, and the rest is the same as Example 3.

[0140]

Example 14

[0141] Compared with Example 3, the only difference is that in the preparation of the solid titanium catalyst component in step (1), 4 grams of magnesium chloride is replaced with 2.4 grams, and everything else is the same as in Example 3.

[0142]

Example 15

[0143] Compared to Example 2, the only difference is that in step (1) the preparation of the solid catalyst component, 68# The amount of white oil added was changed from 0.8 ml to 1.6 ml, and everything else was the same as in Example 2.

[0144]

Example 16

[0145] Compared to Example 2, the only difference is that in step (1) the preparation of the solid catalyst component, 0.8 ml of 68... # The white oil was replaced with 0.72 ml of methyl silicone oil 201 (density 0.955 g / cm³ at 25°C). 3 (kinematic viscosity 55 mPa·s), otherwise the same as in Example 2.

[0146] Comparative Example 1

[0147] Compared with Example 1, the only difference is that 1.71 ml (13.8 mmol) of o-methyl anisole is no longer added in the preparation of the solid titanium catalyst component in step (1), and everything else is the same as in Example 1.

[0148] Comparative Example 2

[0149] Compared with Example 2, the only difference is that 1.71 ml (13.8 mmol) of o-methyl anisole is no longer added in the preparation of the solid titanium catalyst component in step (1), and everything else is the same as in Example 2.

[0150] Comparative Example 3

[0151] Compared with Example 3, the only difference is that 1.71 ml (13.8 mmol) of o-methyl anisole is no longer added in the preparation of the solid titanium catalyst component in step (1), and everything else is the same as in Example 3.

[0152] Comparative Example 4

[0153] Compared to Example 2, the only difference is that 0.8 ml of 68 is no longer added in step (1) during the preparation of the solid titanium catalyst component. # White oil, otherwise the same as in Example 2.

[0154] Comparative Example 5

[0155] Compared to Example 2, the only difference is that in step (1), 1.71 ml (13.8 mmol) of o-methyl anisole and 0.8 ml of 68 were no longer added during the preparation of the solid titanium catalyst component. # White oil, otherwise the same as in Example 2.

[0156] The composition parameters of the solid titanium catalysts prepared in the above embodiments and comparative examples are shown in Table 1 below:

[0157] Table 1

[0158]

[0159] As shown in Table 1, the addition of inert organic compounds and electron-donating compounds to the solid titanium catalyst components of this invention can reduce the tetrahydrofuran content in the catalyst component particles and decrease the D of the catalyst component particles. 10 As the size increases, the number of microparticles decreases.

[0160] The properties of the polymers obtained in the above embodiments and comparative examples are shown in Table 2 below:

[0161] Table 2

[0162]

[0163] As shown in Table 2, compared with the comparative example, the catalyst of the present invention, when used to catalyze ethylene polymerization, produces polyethylene powder with a higher bulk density and polyethylene resin with a lower density. Simultaneously, it exhibits a melt index and catalyst activity comparable to the comparative example, but with a lower content of fine powder (105 micrometers and below). This indicates that the catalyst of the present invention has significant advantages in catalyzing the copolymerization of ethylene and 1-hexene: while maintaining suitable overall catalyst performance, it improves the copolymerization performance of the catalyst, significantly reduces the density of polyethylene resin, and simultaneously increases the bulk density of the powder, thus enhancing the practicality of the catalyst.

[0164] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

[0165] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.

[0166] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.

Claims

1. A solid titanium catalyst composition, characterized in that... The catalyst component is prepared from raw materials comprising the following components: Magnesium halides, titanium-containing compounds, solvents, inorganic oxide carrier fillers, electron-donating compounds, and inert organic compounds; Based on a total weight of 100 wt% of the catalyst components, the content of titanium is 0.1 to 5 wt%. The molar ratio of magnesium to titanium is greater than 2:1; The molar ratio of solvent to magnesium is less than 3:1; The molar ratio of the electron-donating compound to magnesium is less than 3:1; The weight ratio of inert organic compounds to magnesium halides is less than 5:1; The weight ratio of inorganic oxide carrier filler to magnesium halide is less than 4:

1.

2. The catalyst component according to claim 1, characterized in that: Based on a total weight of 100 wt% of the catalyst components, the content of titanium is 0.5 to 3 wt%. The molar ratio of magnesium to titanium is (4-10):1; The molar ratio of solvent to magnesium is (0.5~2):1; The molar ratio of the electron-donating compound to magnesium is (0.1–1.5):1; The weight ratio of inert organic compound to magnesium halide is (0.1–2):1; The weight ratio of inorganic oxide carrier filler to magnesium halide is (0.5~2):

1.

3. The catalyst component according to claim 1 or 2, characterized in that: The catalyst component is a spherical solid particle; preferably, the average diameter of the catalyst component is 2 to 100 μm, more preferably 18 to 30 μm.

4. The catalyst component according to claim 1 or 2, characterized in that: The structural formula of the electron donor compound is: Wherein, X1, X2, X3, X4, and X5 are each independently one of hydrogen, halogen, C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C1-C10 aryl, and C1-C10 aralkyl, and R is one of C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C1-C10 aryl, and C1-C10 aralkyl; preferably, The electron-donating compound is anisole, o-chloroanisole, p-chloroanisole, 2,4-dichloroanisole, m-chloroanisole, o-fluoroanisole, p-fluoroanisole, 2,4-difluoroanisole, m-fluoroanisole, o-bromoanisole, p-bromoanisole, 2,4-dibromoanisole, m-bromoanisole, phenethyl ether, o-chloroanisole, p-chloroanisole, 2,4-dichloroanisole, m-chloroanisole, o-fluoroanisole, p-fluoroanisole. Ethers, 2,4-difluorophenylethyl ether, m-fluorophenylethyl ether, o-bromophenylethyl ether, p-bromophenylethyl ether, 2,4-dibromophenylethyl ether, m-bromophenylethyl ether, isopropyl phenyl ether, o-chlorophenyl isopropyl ether, p-chlorophenyl isopropyl ether, 2,4-dichlorophenyl isopropyl ether, m-chlorophenyl isopropyl ether, o-fluorophenyl isopropyl ether, p-fluorophenyl isopropyl ether, 2,4-difluorophenyl isopropyl ether, m-fluorophenyl isopropyl ether, o-bromophenyl isopropyl ether, p-bromophenyl isopropyl ether, 2,4-Dibromophenylisopropyl ether, m-bromophenylisopropyl ether, phenylbutyl ether, o-chlorophenylbutyl ether, p-chlorophenylbutyl ether, 2,4-dichlorophenylbutyl ether, m-chlorophenylbutyl ether, o-fluorophenylbutyl ether, p-fluorophenylbutyl ether, 2,4-difluorophenylbutyl ether, m-fluorophenylbutyl ether, o-bromophenylbutyl ether, p-bromophenylbutyl ether, 2,4-dibromophenylbutyl ether, m-bromophenylbutyl ether, tert-butyl phenyl ether, o-chlorophenyltert-butyl ether, p-chlorophenyltert-butyl ether The ether is at least one of the following: 2,4-dichlorophenyl tert-butyl ether, m-chlorophenyl tert-butyl ether, o-fluorophenyl tert-butyl ether, p-fluorophenyl tert-butyl ether, 2,4-difluorophenyl tert-butyl ether, m-fluorophenyl tert-butyl ether, o-bromophenyl tert-butyl ether, p-bromophenyl tert-butyl ether, 2,4-dibromophenyl tert-butyl ether, m-bromophenyl tert-butyl ether, diphenyl ether, and phenyl benzyl ether; more preferably, at least one of anisole, o-chloroanisole, isopropyl phenyl ether, and diphenyl ether.

5. The catalyst component according to claim 1 or 2, characterized in that: The titanium-containing compound is at least one of titanium halide and a product of metal reduction of titanium halide; preferably, The titanium halide is at least one selected from titanium tribromide, titanium tetrabromide, titanium trichloride, and titanium tetrachloride; and / or, The product of the metal reduction of titanium halide is at least one selected from the products of aluminum reduction of titanium halide, magnesium reduction of titanium halide, iron reduction of titanium halide, and zinc reduction of titanium halide; more preferably, The chemical formula of the product of aluminum reduction of titanium halide is TiXm·nAlXp, where 0<n≤1, 0<m≤3, 0<p≤3, and X is bromine or chlorine; and / or, The chemical formula of the product of magnesium reducing titanium halide is TiXm'·qMgXr, where 0<q≤1, 0<m'≤3, 0<r≤2, and X is bromine or chlorine.

6. The catalyst component according to claim 1 or 2, characterized in that: The magnesium halide is at least one of magnesium dichloride, magnesium dibromide, and magnesium diiodide; and / or... The inorganic oxide carrier filler is an oxide of silicon and / or an oxide of aluminum, preferably silicon dioxide; more preferably, the particle size of the inorganic oxide carrier filler is 0.01–10 micrometers, preferably 0.01–5 micrometers; even more preferably, the water content of the inorganic oxide carrier filler is 0–2.5%, preferably 0–0.6%; and / or, The solvent is a solvent capable of dissolving the magnesium halide and the titanium-containing compound, preferably at least one selected from diethyl ether, propyl ether, isopentyl ether, tetrahydrofuran, methyltetrahydrofuran, and dioxane; more preferably tetrahydrofuran and / or methyltetrahydrofuran; and / or, The inert organic compound is a liquid hydrocarbon and / or silicone oil; preferably, The liquid hydrocarbon is a C7-C31 alkane with a kinematic viscosity of 1.0-500 mmHg at 40°C. 2 At least one of the white oils with a kinematic viscosity of 60-80 mm at 40°C is preferred. 2 / s of white oil; and / or, The silicone oil has a kinematic viscosity of 5.0-5000 mm at 25°C. 2 / s, preferably at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, ethyl hydrogen silicone oil, and hydroxy hydrogen silicone oil.

7. A method for preparing a solid titanium catalyst component as described in any one of claims 1-6, characterized in that... The method includes: The catalyst component is prepared by mixing magnesium halide, titanium-containing compound, solvent, inorganic oxide support filler, electron donor compound and inert organic compound to form a suspension, followed by spray drying.

8. The method according to claim 7, characterized in that The method includes: (1) Preparation of mother liquor: Under a protective gas atmosphere, solvent, magnesium halide, titanium-containing compound, electron donor compound and inert organic compound are brought into contact to obtain mother liquor; (2) Carrier mixing: In the protective gas atmosphere, inorganic oxide carrier filler is added during or after step (1) to mix and obtain slurry suspension; (3) Spray forming: The slurry suspension is spray dried to obtain the catalyst component.

9. The method according to claim 7 or 8, characterized in that: The molar ratio of the magnesium halide to the titanium-containing compound is greater than 2:1, preferably (4-10):1; and / or, The molar ratio of the solvent to magnesium halide is less than 240:1, preferably (20-40):1; and / or, The molar ratio of the electron donor compound to magnesium halide is less than 3:1, preferably (0.1–1.5):1; and / or, The weight ratio of the inert organic compound to magnesium halide is less than 5:1, preferably (0.1–2):1; and / or, The weight ratio of the inorganic oxide carrier filler to magnesium halide is less than 4:1, preferably (0.5 to 2):

1.

10. The method according to claim 8, characterized in that: In step (1): the contact temperature is 5℃~85℃, and / or the time is ≥0.1 hours; and / or, In step (2): the mixing temperature is 5℃~85℃, and / or the time is ≥0.1 hours; and / or, In step (3): the inlet temperature of the spray dryer is 100–240°C, preferably 120–160°C, and / or the outlet temperature is 60–130°C, preferably 90–115°C, and / or the material feed flow rate is 1–30 ml / min, preferably 5–15 ml / min, and / or the carrier gas and the spray gas can be the same or different, and are independently protective gases, preferably nitrogen, and / or the carrier gas flow rate is 2–40 ml / min. 3 / h, preferably 20-30m 3 / h, and / or, the spray gas flow rate is 5 to 800 L / h, preferably 200 to 500 L / h.

11. A catalyst for olefin polymerization, characterized in that: The catalyst comprises the solid titanium catalyst component as described in any one of claims 1-6 or the solid titanium catalyst component and co-catalyst prepared by the method as described in any one of claims 7-10; The cocatalyst is an organoaluminum compound and / or an incomplete hydrolysis product of an organoaluminum compound; The molar ratio of aluminum in the co-catalyst to titanium in the solid titanium catalyst component is (1-1000):1, preferably (5-200):

1.

12. The catalyst according to claim 11, characterized in that: The chemical formula of the organoaluminum compound is AlR' b X' 3-b Wherein, R' is hydrogen or a C1-C20 hydrocarbon group, preferably a C1-C6 hydrocarbon group, 0 < b ≤ 3, preferably 1 < b ≤ 3, and X' is a halogen, preferably one of chlorine, bromine, and iodine; more preferably, The organoaluminum compound is at least one of trimethylaluminum, triethylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, ethyl sesquichloride aluminum, and dimethylaluminum chloride.

13. The application of a catalyst for olefin polymerization as described in claim 11 or 12 in olefin polymerization; preferably, The olefin polymerization reaction is one of the following: gas-phase polymerization, slurry polymerization, and solution polymerization; and / or... The reaction temperature for the olefin polymerization reaction is 20–120°C, preferably 65–105°C; and / or, The olefin polymerization reaction is a homopolymerization of ethylene or a polymerization reaction of ethylene with at least one α-olefin, preferably a polymerization reaction of ethylene with at least one α-olefin; more preferably, The α-olefin is at least one selected from propylene, butene, pentene, hexene, octene, decene, and 4-methyl-1-pentene.

Citation Information

Patent Citations

  • Process for the preparation of a catalyst component and components therefrom obtained

    CN101050248A

  • Ethylene polymerization catalyst, preparation and application thereof

    CN101885793A

  • Electron donor catalyst and preparation and application

    CN101885795A

  • A catalyst component for ethylene polymerization and the catalyst thereof

    CN102295717A

  • Catalyst component applied to vinyl polymerization reaction and catalyst thereof

    CN102807638A